Mudanças climáticas retardam o envelhecimento de reservatórios neotropicais - Campos, Joana Carneiro de (2017)
Weather may be one of the most important factors influencing species selectivity, since it affects directly the ecosystems. In the last decades extreme climate events have become more frequent. Even though, these events are rare and unusual, they induce a lot of changes in the local weather, as intensifying events of drought and raining, beyond changing the temperature. Rainfall and temperature are the most important factors governing the biology of fish assemblages, in fact, they can influence directly almost all the rates of biological processes. Therefore, changes in the rainfall patterns may modify the rivers hydrology and reservoirs by mutating river floods and droughts regimes, which are important factors influencing the reproduction patterns and trophic dominance in aquatic systems. However, weather isn't only factor influencing the ichthyofauna and other aquatic groups in a Neotropical region. Aquatic ecosystems are also affected by river dams constructions, which may interfere in species life strategies and habitat. Consequently, we expect to found older reservoirs, in this type of environmental, concentrating a high abundance of sedentary species with higher feeding plasticity, since the reservoir aging process provide environmental changes that function as a filter for some functional traits. Therefore, your hypothesis is that changes on local weather may influence the water temperature consequently it will affect the fishes habitat quality, so any extreme change in the air temperature levels and rainfall will disturb the fish assemblages. Thus, the main objective with this thesis was to evaluate if the changes occurring in the regional weather during the beginning of 2000s had influence in the fish assemblage trophic reorganization in the Neotropical reservoirs. Our results showed that the local climate shifts, recorded during the study period, had effect in the fish assemblage organization as did the modifications caused by the reservoirs aging processes.